An update on malignant tumor-related stiff person syndrome spectrum disorders: clinical mechanism, treatment, and outcomes - Peng, Yong; Yang, Huan; Xue, Ya-hui; Chen, Quan; Jin, Hong; Liu, Shu; Yao, Shun-yu; Du, Miao-qiao (Frontiers in Neurology, 2023)
Stiff person syndrome (SPS) is a rare central nervous system disorder associated with malignancies. In this review, we retrieved information from PubMed, up until August 2023, using various search terms and their combinations, including SPS, stiff person syndrome spectrum disorders (SPSSDs), paraneoplastic, cancer, and malignant tumor. Data from peer-reviewed journals printed in English were organized to explain the possible relationships between different carcinomas and SPSSD subtypes, as well as related autoantigens. From literature searching, it was revealed that breast cancer was the most prevalent carcinoma linked to SPSSDs, followed by lung cancer and lymphoma. Furthermore, classic SPS was the most common SPSSD subtype, followed by stiff limb syndrome and progressive encephalomyelitis with rigidity and myoclonus. GAD65 was the most common autoantigen in patients with cancer and SPSSDs, followed by amphiphysin and GlyR. Patients with cancer subtypes might have multiple SPSSD subtypes, and conversely, patients with SPSSD subtypes might have multiple carcinoma subtypes. The first aim of this review was to highlight the complex nature of the relationships among cancers, autoantigens, and SPSSDs as new information in this field continues to be generated globally. The adoption of an open-minded approach to updating information on new cancer subtypes, autoantigens, and SPSSDs is recommended to renew our database. The second aim of this review was to discuss SPS animal models, which will help us to understand the mechanisms underlying the pathogenesis of SPS. In future, elucidating the relationship among cancers, autoantigens, and SPSSDs is critical for the early prediction of cancer and discovery of new therapeutic modalities.